Kesehatan telinga siswa di SMP Negeri 4 Pineleng - Montilei, Vania F.; Pelealu, Olivia C.P.; Palandeng, Ora I. (e-CliniC, 2016)
Abstract: Around 20% of information were obtained from both ears daily. Hearing problem in children is sometimes hard to be detected and can cause difficulties in learning process. This study was aimed to obtain the ear health status of students at SMP Negeri 4 Pineleng (junior high school). This was a descriptive observational study with a cross-sectional design. Respondents were 25 students of class IX A. Meatus acoustic external was examined by an otorhinolaryngologist and then the data were processed by using Microsoft Excel. Based on the screening of hearing function, all students showed normal result. Ear canal examination showed that 3 students had cerumen in the right and left ear canals, and 1 student had hyperemia in the left ear. Perforated tympanic membrane were obtained in 2 students in the right and left ear canals. All students had normal Rinne test meanwhile Weber test showed 2 students with lateralization to the right and 1 student with lateralization to the left. Conclusion: Students at SMP Negeri 4 Pineleng had good ear health status.. Keywords: ear health, hearing screeningÂ Abstrak: Telinga dapat menyerap sebesar 20% informasi dari kehidupan sehari-hari. Gangguan pendengaran pada anak sulit dideteksi yang berakibat anak sulit untuk menerima pelajaran. Penelitian ini bertujuan untuk mengetahui status kesehatan telinga pada siswa SMP Negeri 4 Pineleng. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Responden penelitian ialah 25 orang siswa kelas IX A. Pengambilan data dilakukan dengan pemeriksaan meatus akustikus eksterna oleh dokter spesialis bagian THT-KL, kemudian diolah dengan Microsoft Excel. Hasil skrining pendengaran dari seluruh siswa ialah normal. Pemeriksaan liang telinga didapatkan 3 siswa dengan serumen di telinga kanan dan kiri, serta 1 siswa dengan hiperemis di telinga kiri. Pemeriksaan membran timpani didapatkan perforasi pada 2 siswa, 1 ditelinga kanan dan 1 ditelinga kiri. Hasil tes Rinne semuanya normal. Pada tes Weber didapatkan 2 siswa dengan lateralisasi ke kanan dan 1 siswa lateralisasi ke kiri. Simpulan: Kesehatan telinga siswa di SMP 8 Pineleng cukup baik.Kata kunci: kesehatan telinga, skrining pendengaran